Antibacterial activity of hydrogen peroxide and the lactoperoxidase-hydrogen peroxide-thiocyanate system against oral streptococci. - Thomas, E L (1994)
In secreted fluids, the enzyme lactoperoxidase (LP) catalyzes the oxidation of thiocyanate ion (SCN-) by hydrogen peroxide (H2O2), producing the weak oxidizing agent hypothiocyanite (OSCN-), which has bacteriostatic activity. However, H2O2 has antibacterial activity in the absence of LP and thiocyanate (SCN-). Therefore, LP may increase antibacterial activity by using H2O2 to produce a more effective inhibitor of bacterial metabolism and growth, or LP may protect bacteria against the toxicity of H2O2 by converting H2O2 to a less-potent oxidizing agent. To clarify the role of LP, the antibacterial activities of H2O2 and the LP-H2O2-SCN- system were compared by measuring loss of viability and inhibition of bacterial metabolism and growth. The relative toxicity of H2O2 and the LP system to oral streptococci was found to depend on the length of time that the bacteria were exposed to the agents. During incubations of up to 4 h, the LP system was from 10 to 500 times more effective than H2O2 as an inhibitor of glucose metabolism, lactic acid production, and growth. However, if no more H2O2 was added, the concentration of the inhibitor OSCN- fell because of slow decomposition of OSCN-, and when OSCN- fell below 0.01 mM, the bacteria resumed metabolism and growth. In contrast, the activity of H2O2 increased with time. H2O2 persisted in the medium for long periods of time because H2O2 reacted slowly with the bacteria and streptococci lack the enzyme catalase, which converts H2O2 to oxygen and water. After 24 h of exposure, H2O2 was as effective as the LP system as an inhibitor of metabolism. H2O2 also caused a time-dependent loss of viability, whereas the LP system had little bactericidal activity. The concentration of H2O2 required to kill half the bacteria within 15 s was 1.8 M (6%) but fell to 0.3 M (1%) at 2 min, to 10 mM (0.03%) at 1 h, and to 0.2 mM (0.0007%) with a 24-h exposure. The results indicate that if high levels of H2O2 can be sustained for long periods of time, H2O2 is an effective bactericidal agent, and the presence of LP and SCN- protects streptococci against killing by H2O2. Nevertheless, the combination of LP, H2O2, and SCN- is much more effective than H2O2 alone as an inhibitor of bacterial metabolism and growth.